SEAWATER QUALITY FOR SHRIMP MARICULTURE BASED ON MICROBIOLOGY PARAMETERS - Lies Indah Sutiknowati (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
Seawater quality plays an important factor for the success of mariculture such as microbiology paramater. The research aimed  to analize the waters quality for shrimp mariculture in Barru, Pangkep, and Maros based on bacteriology parameters.  The research were carried out in June 2012. Bacteriology parameters analysed were total coliform, E.coli, pathogen, heterotrophic, halotolerant, and phosphate-nitrate-ammonia bacteria. Coliform and E.coli bacteria were analysed based on filtration. Pathogenic bacteria was identified using biochemical test. Heterotrophic, halotolerant, and phosphate-nitrate-ammonia bacteria were analysed using pour plate. The results from shrimp aquaculture showed the total abundance of coliform cell of >1000 colony forming unit (cfu)/100 ml, E.coli of 0-4 cfu/100ml, heterotrophic bacteria of about (31-176)x103 cfu/ml, and halotolerant bacteria of about (31-375)x103 cfu/ml. The results from sediment for heterotrophic bacteria was about (350-3920)x103 cfu/ml, halotolerant of about (350-4980)3x10 cfu/ml, and phosphate-nitrate-ammonia bacteria of about 14-46 cfu/ml. The pathogen bacteria waere found such as genus Aeromonas, Pseudomonas, Proteus, Citrobacter, Shigella and Yersinia. The dominant pathogens in shrimp aquaculture water and sediment were Proteus and Citrobacter. The results indicated that seawaters in Barru, Pangkep, and Maros can be used for mariculture including shrimp Panaeid. Keywords: bacteria, parameter, marineculture, shrimp.